Preparation and Characterization of Zinc doped Magnetite Nanoparticles using Green Synthesis - Lahure Pranita; Jain Preeti (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
Zinc doped Nanomagnetite was synthesized in lab by biological method using plant extract as it does not involve any harmful chemicals and are ecofriendly in nature. In the present work, zinc doped magnetite nanoparticles were synthesized using completely green synthesis by chemical route method. The band- gap of the zinc doped Fe3O4-NPs was investigated by UV-Vis Absorption Spectroscopy, grain size is calculated using XRD and its energy shifting was studied by FTIR , also its conductivity (i.e. the ability or power to conduct or transmit heat, electricity, or sound) was measured by TDS Conductivity meter. The doped nanoparticles synthesized through this green method can potentially useful in various biomedical applications.